VD_FINDINFO HC / 2015 / 815 vom 16. September 2015 - VD Tribunal cantonal (2015)
DROIT DE GARDE, APPRÉCIATION DES PREUVES, MOTIVATION DE LA DEMANDE | 133 CC, 176 al. 3 CC, 157 CPC (CH), 276 al. 1 CPC (CH), 308 al. 1 let. b CPC (CH), 308 al. 2 CPC (CH), 311 al. 1 CPC (CH), 316 al. 3 CPC (CH)